The PROBA2 Mission 2013
DOI: 10.1007/978-1-4614-8187-4_3
|View full text |Cite
|
Sign up to set email alerts
|

The LYRA Instrument Onboard PROBA2: Description and In-Flight Performance

Abstract: The Large Yield Radiometer (LYRA) is an XUV-EUV-MUV (soft X-ray to mid-ultraviolet) solar radiometer onboard the European Space Agency PROBA2 mission that was launched in November 2009. LYRA acquires solar irradiance measurements at a high cadence (nominally 20 Hz) in four broad spectral channels, from soft X-ray to MUV, that have been chosen for their relevance to solar physics, space weather and aeronomy. In this article, we briefly review the design of the instrument, give an overview of the data products d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 26 publications
0
11
0
Order By: Relevance
“…To analyze the correlation of the noise attenuation with various solar radiation lines, we carried out a joint analysis of the absorption during the 80 flares of 2013–2017 and data from varied instruments, namely: GOES/XRS (Hanser & Sellers, ; Machol & Viereck, ), GOES/EUVS (Machol et al, ), SDO/AIA (Lemen et al, ), PROBA2/LYRA (Dominique et al, ; Hochedez et al, ), SOHO/SEM (Didkovsky et al, ), and SDO/EVE(ESP; Didkovsky et al, ). These instruments provide direct and regular observations of solar radiation in the wavelength range 1–2,500 Å during the period under study (see Table S2 in the supporting information for details).…”
Section: Correlation Of Absorption Dynamics With Solar Radiation Of Dmentioning
confidence: 99%
“…To analyze the correlation of the noise attenuation with various solar radiation lines, we carried out a joint analysis of the absorption during the 80 flares of 2013–2017 and data from varied instruments, namely: GOES/XRS (Hanser & Sellers, ; Machol & Viereck, ), GOES/EUVS (Machol et al, ), SDO/AIA (Lemen et al, ), PROBA2/LYRA (Dominique et al, ; Hochedez et al, ), SOHO/SEM (Didkovsky et al, ), and SDO/EVE(ESP; Didkovsky et al, ). These instruments provide direct and regular observations of solar radiation in the wavelength range 1–2,500 Å during the period under study (see Table S2 in the supporting information for details).…”
Section: Correlation Of Absorption Dynamics With Solar Radiation Of Dmentioning
confidence: 99%
“…In this paper, new 150 to 400 km thermospheric density profiles are presented that were observed over the winter hemisphere by the 1–20 nm Zr channel of the solar observing Large Yield Radiometer (LYRA) instrument (Dominique et al, ; Hochedez et al, ) on the European Space Agency (ESA) PROBA2 satellite (Santandrea et al, ) between 2010 and 2017. It is shown that full‐disk solar irradiance measurements from the Zr channel are suitable for measuring the summed O and N 2 number density at approximately 5 km resolution to within 15% absolute accuracy.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is essential that instruments either measure the identical range (for continuity) or have sufficient resolution to accurately reconstruct it. This requirement excludes certain instruments for thermosphere modeling purposes (e.g., the Large Yield Radiometer, Dominique et al, , aboard the PROBA2 spacecraft). A crucial disadvantage of satellite EUV measurements and therefore also He II‐based proxies is, besides calibration and cross‐calibration issues due to different instruments, that the main composition measurements we have were taken by Dynamics Explorer 2 in the early 1980s and the Atmosphere Explorer (AE‐C, AE‐D, and AE‐E) in the 1970s.…”
Section: Euv Irradiance and Its Proxiesmentioning
confidence: 99%